Perbedaan Heritabilitas Infeksi Heterakis gallinarum pada Ayam Lokal dan Ras Lohman - Prayoga, I Made Angga; Suratma, Nyoman Adi; Damriyasa, I Made (Buletin Veteriner Udayana, 2014)
The study was couducted to determine the difference of heritability of Heterakis gallinarum in local and Lohman chicken. Sixteen local chicken and 16 Lohman chicken were inoculated with infected egg of Heterakis gallinarum for 250 egg in ech chicken. All chiken were necropsed 3 months after inoculated. The heritabilty of the worm was evaluated by determinan the number of infected chicken and number of worms. There were found 10 local chicken infected by Heterakis gallinarum and 2 local chicken infected by the worm. The result of the study indicated that the heratibility of Heterakis gallinarum is  higher in local chicken than Lohman chicken.
Keywords: Heritability, Heterakis gallinarum, local chicken and Lohman chicken